The impact of moral leadership on physical education teachers’ innovation behavior: The role of identification with leader and psychological safety - Chen, Jineng; Zheng, Wei; Jiang, Binbin (Frontiers in Psychology, 2022)
With the growth of people’s health needs and the impact of the COVID-19 pandemic, it is an inevitable trend to promote innovation behaviors of physical education (PE) teachers to innovate traditional physical education and adapt to national needs of sustainable development in the sports industry. Considering that moral leadership can promote innovation behavior of individuals through psychological factors, this study defines the types of innovation behavior, and from the perspective of psychological safety and identifying with leaders, discusses the impact of moral leadership on individuals’ innovation behavior by using hierarchical multivariate regression analysis, which provides inspiration for schools to strengthen the innovation behavior of physical education teachers. In this study, 327 questionnaires were distributed to PE teachers in Chinese provinces and 287 valid questionnaires were collected. The analysis of the collected data was performed with the help of the SPSSAU data analysis platform. The following conclusions were drawn: First, moral leadership has a significant positive impact on the psychological safety and internal and external innovation of physical education teachers. Secondly, moral leadership influences employees’ innovation behavior through psychological safety, and plays a part of intermediary role between moral leadership and internal and external innovation behavior; Third, by comparing the two impact mechanisms of innovation behavior, we found that moral leadership encourages employees to produce more external innovation behavior through psychological safety; Finally, strong leadership identity plays a positive role in regulating the relationship between moral leadership and innovation behavior.